Comparator effect on equivalence of results of calibrating current transformers - Isaiev, Valentyn; Velychko, Oleh; Anokhin, Yurii (Eastern-European Journal of Enterprise Technologies, 2019)
Many different high-precision systems for determining the ratio error and phase displacement of current transformers have been developed by leading specialists in the world. The latest research solutions with the use of the latest measurement tools, instantaneous sampling techniques, and analysis of sources of uncertainty have been applied in these developments. The objective difficulty is that only a limited number of specialized institutes implement such projects with the involvement of leading experts in the field of measurement and significant funds. First of all, these are the national metrological institutes of countries with high economic opportunities. At the level of conventional calibration laboratories equipped with modern facilities and highly qualified personnel, the uncertainty of measurements increases 10 times or more when calibrating precision instrument transformers. Thus, it has not been investigated to what extent the readouts of commercial comparators of different manufacturers in the calibration of instrument transformers of class 0.2S and more precise are equivalent. Determination of the equivalence level of AC comparators of different types in the day-to-day calibration of current transformers is the main objective of this research. More than 50 comparators of different types (with inductive or resistive current transducers) were investigated relative to 2 well-characterized reference current transformers. Comparison of the results obtained by two instruments with radically different principles of measurement gave a difference of 23 μA/A in ratio error and 52 μrad in phase displacement. The results of estimating the readout stability of modern comparators of serial production are also highlighted. The results of the analysis of the data obtained allow us to assume that measurement results of ratio error of about 50 μA/A have equivalence level within ±20 μA/A. The measurement results of phase displacement of about 50 μrad have equivalence level within ±15 μrad. Concerning the determination of metrological characteristics of current transformers with accuracy class 0.2S, their equivalence must be considered taking into account all exploited comparators. The results cause the question about the adequacy of the accuracy margin of the current transformer in the production to overlap the difference in the readouts of 260 μA/A and 500 μrad